WINNING MECHANISMS OF SURVIVAL: A CASE OF “BUL-ANON” RETAILERS IN RURAL PHILIPPINES - Bisnar, Charlotte; Neoy, Lisa; Villamor, Mary Crist; Gil-Salapi, Candy Elizabeth (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2024)
This study focused on the challenges faced by a group of independent and small retailers called Bul-anon retailers and identified coping mechanisms adopted. The study was conducted to investigate the coping mechanisms that can be utilized by other members of the retail industry to continue to thrive despite difficulties. Findings indicated that the challenges faced by the Bul-anon retailers revolved around three of the four primary business functions: marketing, finance/accounting, and operations. To avoid the significant impact of the above challenges, retailers adopted coping mechanisms to stay in business amidst large department stores and other businesses. How they handled their customers, being customer-oriented, was the winning mechanism for the survival of these retailers.